Systematic and functional analysis of non-specific lipid transfer protein family genes in sugarcane under Xanthomonas albilineans infection and salicylic acid treatment - Li, Juan; Zhao, Jian-Ying; Shi, Yang; Fu, Hua-Ying; Huang, Mei-Ting; Meng, Jian-Yu; Gao, San-Ji (Frontiers in Plant Science, 2022)
Plant non-specific lipid transfer proteins (nsLTPs) are small basic proteins that play a significant regulatory role in a wide range of physiological processes. To date, no genome-wide survey and expression analysis of this gene family in sugarcane has been performed. In this study we identified the nsLTP gene family in Saccharum spontaneum and carried out expression profiling of nsLTPs in two sugarcane cultivars (Saccharum spp.) that have different resistance to leaf scald caused by Xanthomonas albilineans (Xa) infection. The effect of stress related to exogenous salicylic acid (SA) treatment was also examined. At a genome-wide level, S. spontaneum AP85-441 had 71 SsnsLTP genes including 66 alleles. Tandem (9 gene pairs) and segmental (36 gene pairs) duplication events contributed to SsnsLTP gene family expansion. Five SsnsLTP proteins were predicted to interact with five other proteins. Expression of ShnsLTPI.8/10/Gb.1 genes was significantly upregulated in LCP85-384 (resistant cultivar), but downregulated in ROC20 (susceptible cultivar), suggesting that these genes play a positive regulatory role in response of sugarcane to Xa infection. Conversely, ShnsLTPGa.4/Ge.3 appears to act as a negative regulator in response Xa infection. The majority (16/17) of tested genes were positively induced in LCP85-384 72 h after SA treatment. In both cultivars, but particularly in LCP85-384, ShnsLTPIV.3/VIII.1 genes were upregulated at all time-points, suggesting that the two genes might act as positive regulators under SA stress. Meanwhile, both cultivars showed downregulated ShnsLTPGb.1 gene expression, indicating its potential negative role in SA treatment responses. Notably, the ShnsLTPGb.1 gene had contrasting effects, with positive regulation of gene expression in response to Xa infection and negative regulation induced by SA stress. Together, our results provide valuable information for elucidating the function of ShnsLTP family members under two stressors and identified novel gene sources for development of sugarcane that are tolerant of environmental stimuli.